THE ROLE OF FINANCIAL INSTITUTIONS FOR THE DEVELOPMENT OF THE SECURITIES MARKET - Fufalko , I. Yu. (The actual problems of regional economy development, 2016)
The article investigates the role of financial institutions such as banks, insurance companies and collective investment institutions in the financial market of Ukraine and the European Union, and determines the impact of each of them on the securities market. Analysing the structure of financial markets of the EU and Ukraine was determined the share of assets of every type of financial institutions. This allowed us to estimate their role on financial market. Moreover, analyses of the assets` proportions that are invested on the stock market has allowed us to see the financial institutions` importance for the securities market. It was determined that, despite the banking model of the financial market in EU, role of banks for the securities market development is not decisive. A significant share of assets placed in securities by the insurance companies and shadow banking sector or, as it is called in Ukraine, collective investment institutions. The two last-mentioned sectors are underdeveloped in the Ukrainian financial market. This explains the lack of development of securities market of Ukraine. JEL: G 20